A clinically realistic large animal model of intra-articular fracture that progresses to post-traumatic osteoarthritis. Issue 10 (October 2015) - Goetz, J.E.; Fredericks, D.; Petersen, E.; Rudert, M.J.; Baer, T.; Swanson, E.; Roberts, N.; Martin, J.; Tochigi, Y.
Summary: Objective: Translation of promising treatments for post-traumatic osteoarthritis (PTOA) to patients with intra-articular fracture (IAF) has been limited by the lack of a realistic large animal model. To address this issue we developed a large animal model of IAF in the distal tibia of Yucatan minipigs and documented the natural progression of this injury. Design: Twenty-two fractures were treated using open reduction and internal fixation with either an anatomic reduction or an intentional 2-mm step-off. Pre-operatively, and 3 days, 1, 2, 4, 8, and 12 weeks post-operatively, animals were sedated for synovial fluid draws and radiographs. Limb loading was monitored at the same time points using a Tekscan Walkway. Animals were sacrificed at 12 weeks and the limbs were harvested for histological evaluation. Results: All animals achieved bony union by 12 weeks, facilitating nearly complete recovery of the initial 60% decrease in limb loading. TNFα, IL1β, IL6, and IL8 concentrations in the fractured limbs were elevated ( P < 0.05) at specific times during the 2 weeks after fracture. Histological cartilage degeneration was more severe in the step-off group (0.0001 < P < 0.27 compared to normal) than in the anatomic reconstruction group (0.27 < P < 0.99 compared to normal). Conclusions: This model replicated key features of a human IAF, including surgical stabilization, inflammatory responses, and progression to osteoarthritic cartilage degeneration, thereby providing a potentially useful model for translating promising treatment options to clinical practice.